2021
DOI: 10.3390/antibiotics10030228
|View full text |Cite
|
Sign up to set email alerts
|

Impact of On-Farm Interventions against CTX-Resistant Escherichia coli on the Contamination of Carcasses before and during an Experimental Slaughter

Abstract: Cefotaxime (CTX)-resistant Enterobacteriaceae are still an ongoing challenge in human and veterinary health. High prevalence of these resistant bacteria is detected in broiler chickens and the prevention of their dissemination along the production pyramid is of major concern. The impact of certain on-farm interventions on the external bacterial contamination of broiler chickens, as well as their influence on single processing steps and (cross-) contamination, have not yet been evaluated. Therefore, we investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…References [71,72,82,83], as well as the study by [79], showed that prolonged usage of specific acids in a food facility may facilitate the development of resistant strains. As there are currently insufficient data available on microorganisms resistant to OAs, this situation should be monitored and controlled.…”
Section: Discussionmentioning
confidence: 99%
“…References [71,72,82,83], as well as the study by [79], showed that prolonged usage of specific acids in a food facility may facilitate the development of resistant strains. As there are currently insufficient data available on microorganisms resistant to OAs, this situation should be monitored and controlled.…”
Section: Discussionmentioning
confidence: 99%
“…If the largest part of resistant bacteria in humans are attributable to livestock (and to the corresponding foods), this might suggest that focusing on animals in order to reduce resistances might be the most effective thing to do. This could include studying mitigating strategies against the spread of resistant bacteria in livestock like for example veterinarian antimicrobial (also called antibiotic) stewardship [15][16][17] or husbandry practices [18,19]. If, on the other hand, the largest part of resistances circulates within human populations then this might suggest that it is more effective focusing on the human side in order to mitigate the rise of resistant strains of bacteria (again for example through antibiotic stewardship [20]).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting 1.46-log 10 reduction means then that the external contamination has been reduced by a factor of 10 −1.46 = 0.034. Since the log reduction is a relative measure of reduction this 1.46-log 10 reduction is independent of the units used for the absolute counts (measured in cfu/sqcm by Projahn et al (2021) or cfu/carcass by our processing model). The log reduction applies to both units in the same way, namely it describes a reduction of the bacterial counts by a factor of 0.034.…”
Section: Intervention Process Modelmentioning
confidence: 99%
“…At farm level Competitive exclusion 0.72 ± 0.20 (A) (Projahn et al, 2021) Reduced stocking density 1.46 ± 0.22 (A) (Projahn et al, 2021) Pre-processing Brush breast/vent 0.30 ± 0.10 (A) (Pacholewicz et al, 2016) Cloacal plugging 0.39 ± 0.08 (A) (Musgrove et al, 1997) Scalding Immersion scalding 59.5 • C for 2.5 min 1.57 ± 0.09 (R) (Notermans et al, 1975) Immersion scalding 62.5 • C for 2.5 min 3.00 ± 0.09 (R) (Notermans et al, 1975) Immersion scalding 65.8 • C for 2.5 min 4.00 ± 0.09 (R) (Notermans et al, 1975) Counterflow triple tank 2.60 ± 0.10 (R) (Berrang et al, 2003) Defeathering Hot water rescald 0.50 ± 0.33 (A) (Berrang et al, 2000) Hot water spray 0.70 ± 0.33 (A) (Berrang et al, 2000) Evisceration Skin removal 1.40 ± 0.10 (A) (Berrang et al, 2002) Washing High pressure spray wash (1000 kPa) 0.56 ± 0.14 (R) (Giombelli, 2013) Steam treatment 100 • C for 5 sec 1.44 ± 0.30 (R) (James et al, 2007) Steam treatment 100 • C for 10 sec 1.60 ± 0.07 (R) (James et al, 2007) Steam treatment 100 • C for 12 sec 2.26 ± 0.33 (R) (James et al, 2007) Steam treatment 100 • C for 20 sec 2.83 ± 0.30 (R) (James et al, 2007) Steam treatment 138 • C for 1.1 sec 1.27 ± 0.03 (R) (Kozempel et al, 2003) Hot water 80 • C for 10 sec 0.94 ± 0.18 (R) (James et al, 2007) Hot water 80 • C for 20 sec 1.68 ± 0.12 (R) (James et al, 2007) Chilling Salting 1.77 ± 0.24 (A) (Shin et al, 2012) Crust freezing 0.80 ± 0.52 (R) (Chaves et al, 2011;James et al, 2007) Immersion chilling 1.00 ± 0.25 (R) (Berrang et al, 2008;Chaves et al, 2011;Dickens et al, 2000;James et al, 2007;Souza et al, 2012) for the mean 4.5 cfu/g the standard deviation was set to 0.59 cfu/g feces.…”
Section: Stage Intervention Mean Log 10 Reduction Referencementioning
confidence: 99%